Twentieth century forcible child transfers : probing the boundaries of the genocide convention - Amir, Ruth (Lexington Books, 2019)
Genocidal forcible child transfer -- Genocide -- The forcible transfer clause -- Historical cases -- Forcible child transfers colonialism -- Forcible transfer of immigrant children -- Forcible transfers of republican children in Spain -- Conclusion -- Genocide of political groups and forcible child transfers -- Conclusion -- Bibliography -- Index -- About the author.